The Effect of Peer Support and Supervisor Support on Employee Performance Mediated by Teamwork Cohesiveness - Jihan Azizah; Fauji Sanusi; Roni Kambara (International Journal of Economics, Business and Innovation Research, 2026)
This study aims to analyze the influence of peer support and supervisor support on employee performance with teamwork cohesiveness as a mediating variable at Citra Purnama Catering. The research method used is quantitative with an explanatory research design. The study population was 90 employees, with a sample of 84 operational employees determined using a saturated sampling technique. Data in this study were collected through distributing questionnaires with a measurement scale of 1-10 and analyzed using SmartPLS 3.0 software. The results showed that peer support had a positive and significant effect on employee performance, while supervisor support had a positive but insignificant effect on employee performance. Teamwork cohesiveness had a positive and significant effect on employee performance. In addition, peer support and supervisor support had a positive and significant effect on teamwork cohesiveness. Teamwork cohesiveness was proven to partially mediate the relationship between peer support and employee performance, and fully mediate the relationship between supervisor support and employee performance.